Investigate the Function and Structure of (Fe,Cr) La2Ti2O7 Photocatalyst Calcined under the Nitrogen Atmosphere - Hussanai Luangthanarak; Ratchadaporn Supruangnet; Waraporn Tanthanuch; Sukasem Watcharamaisakul (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Extensive research has been conducted on enhancing the photocatalytic activity of Lanthanum titanium oxide (La2Ti2O7) based photocatalysts. However, these photocatalysts were found to be inactive under visible light. To address this limitation, a modification was developed by co-doping Fe and Cr on La2Ti2O7 to enable visible light driven photocatalytic response. The calcination of (Fe,Cr) La2Ti2O7 was carried out under nitrogen atmosphere at various temperatures for 24 h. The results showed that the (Fe,Cr)-La2Ti2O7 calcined at 1250 °C for 24 h exhibited the highest methylene blue degradation under visible light. Synchrotron X-ray absorption spectroscopy indicated that Fe and Cr were substitutionally located adjacent to the Ti atom within the La2Ti2O7 structure. This metal substitutionally facilitated electron transfer and perturbed the p-d hybridization by modifying the local electronic structure of the surrounding oxygen atoms and transition metal ions, thereby reducing the band gap energy and enhancing the photocatalytic capability. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).